Pouvoir se reposer au cours du poste de nuit : un atout pour le travail ? - Ghislaine Tirilly; Béatrice Barthe; Catherine Gentil (Perspectives Interdisciplinaires sur le Travail et la Santé)
This study explored the general discussion concerning the organization of night shifts. More precisely, it looked at whether spontaneous rest periods taken during the night shift had beneficial effects on work. The study was carried out in a hospital cardiology intensive care unit in which two permanent alternating night work teams were followed. Data was assessed by means of systematic observations, sleep diaries, sleepiness scales (KSS), and self-assessed care quality scores (analogical scales and questionnaires). The study found that rest breaks were associated with a noticeable improvement in the perception of work at the end of the shift. This result raises questions about the current organization, especially concerning the shift handover. The importance of taking into account care activity and patient and institutional viewpoints in future research should be discussed.